Transforming performance appraisal through appreciative inquiry - Buckham, Robert H. (Estudios de Administración, 2018)
As an essential organizational process, performance appraisal effectiveness remains an unrealized hope. The research question addressed here is can Appreciative Inquiry (Cooperrider and Whitney, 2000) alter an organization’s performance appraisal narrative? This qualitative field study offers an innovative enhancement to Murphy and Cleveland’s (1995) performance appraisal communication model by incorporating Appreciative Inquiry as a meta-narrative transformative intervention. Results showed that organization members interpret individual performance appraisal experiences in light of the organization’s overall performance meta-narrative. Further, employee interpretations can be positively influenced when they are encouraged to adopt an affirming and hopeful lens that honors performance appraisal’s cultural inheritance. The outcomes are attributed to a few organization members dreaming of the process at its best based on previous positive experiences and then expressing their vision in wider and wider circles of sharing. Although based on a small, convenience sample, this intervention also indicated Appreciative Inquiry may offer unique and helpful advantages in performance appraisal research.